Evaluation of novel leaching assessment of nuclear waste glasses. (27th December 2016) - Thorpe, Clare L.; Hand, Russell J.; Hyatt, Neil C.; Kruger, Albert A.; Kosson, David S.; Schweiger, Michael J.; Riley, Brian J.; Corkhill, Claire L.
ABSTRACT: This study investigates the use of 'simple' glasses, comprising six components, to represent the structure of complex LAW glasses proposed for Immobilized Low Activity Wastes from the Hanford site in the USA. The 18 elements present in ILAW glasses LAW A44, ORP LB2, and LAW A23 were represented by Al2 O3, B2 O3, CaO, Na2 O, SiO2, and ZrO2 according to their coordination chemistry and their roles as network formers and modifiers. The dissolution behavior of each 'simple' glass was compared to its corresponding candidate "complex" LAW glass through PCT-B tests. Significant differences were observed; the durability of complex glasses was concluded to be LAW A44 > ORP LB2 ≥ LAW A23 whereas in their simplified versions the order was LAW A44 > LAW A23 > ORP LB2. These results are discussed in relation to compositional differences and highlight the importance of minor glass components in controlling glass durability. The implications of these results for the use of simplified glass compositions are discussed.